PENGARUH PRODUCT QUALITY TERHADAP REPURCHASE INTENTION YANG DIMEDIASI OLEH CUSTOMER SATISFACTION PIXY COMPACT POWDER DI KOTA BANDUNG - D. Mega Nursolihah; Dian Lestari (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to investigate the impact of product quality on repurchase intention, mediated by customer satisfaction with Pixy compact powder in the city of Bandung. The research instruments used have undergone thorough testing for validity and reliability. These instruments were employed in collecting data from respondents who have used Pixy compact powder at least once in the past year. The research sample comprises 120 respondents. The data analysis methods applied include quantitative descriptive analysis, simple regression, multiple regression, utilizing SPSS version 26, and employing the Sobel test. All four proposed hypotheses are supported by empirical research data. The findings indicate that customer satisfaction plays a mediating role in the relationship between product quality and repurchase intention. The implications of this research are expected to contribute to future studies and provide valuable insights for Pixy company's strategies in enhancing its quality attributes.